Using network science in the language sciences and clinic - Vitevitch, Michael S. (Int J Speech Lang Pathol, 2014)
A number of variables—word frequency, word length—have long been known to influence language processing. We briefly review the effects in speech perception and production of two more recently examined variables: phonotactic probability and neighborhood density. We then describe a new approach to study language, network science, which is an interdisciplinary field drawing from mathematics, computer science, physics, and other disciplines. In this approach, nodes represent individual entities in a system (i.e., phonological word-forms in the lexicon), links between nodes represent relationships between nodes (i.e., phonological neighbors), and various measures enable researchers to assess the micro-level (i.e., the individual word), the macro-level (i.e., characteristics about the whole system), and the meso-level (i.e., how an individual fits into smaller sub-groups in the larger system). Although research on individual lexical characteristics such as word-frequency has increased our understanding of language processing, these measures only assess the “micro-level.” Using network science, researchers can examine words at various levels in the system, and how each word relates to the many other words stored in the lexicon. Several new findings using the network science approach are summarized to illustrate how this approach can be used to advance basic research as well as clinical practice.